2021
DOI: 10.1155/2021/8826063
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Regional Clay: Application to Phenol Adsorption

Abstract: Phenol is one of the most toxic pollutants found in industrial waste. This work focuses on the removal of phenol using clay from the Sale region. Adsorbent was characterized by X-ray fluorescence spectroscopy, X-ray diffraction, infrared spectroscopy, and scanning electron microscopy. The chemical analysis of this clay shows that the percentage of silicon and aluminium is quite high, and the percentage of calcium and iron is relatively high, so this material is rich in muscovite, quartz, and calcite. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Because of this, negatively charged nanoparticles such as GO can benefit from the favorable adsorption surfaces offered by montmorillonite colloids, allowing for more control over GO’s environmental fate. Chrysikopoulos et al [ 24 ] indicated that GO nanoparticle retention enhanced when decreasing the pH of the solution by boosting hetero-aggregation between GO nanoparticles, which was in line with other findings [ 25 ]. Furthermore, ref.…”
Section: Introductionsupporting
confidence: 84%
“…Because of this, negatively charged nanoparticles such as GO can benefit from the favorable adsorption surfaces offered by montmorillonite colloids, allowing for more control over GO’s environmental fate. Chrysikopoulos et al [ 24 ] indicated that GO nanoparticle retention enhanced when decreasing the pH of the solution by boosting hetero-aggregation between GO nanoparticles, which was in line with other findings [ 25 ]. Furthermore, ref.…”
Section: Introductionsupporting
confidence: 84%
“…The band at 540 and 827 cm −1 in the NC is due to the Zn-O bond. This band is also due to the Al-O and Si-O bond in the NC, indicating the presence of aluminates and silicates coming from clay [65,66]. The bands at 1627 and 1875 cm −1 in ZnONPs and the NC are assigned to the OH group available in the materials.…”
Section: Ftir Analysis Of Znonps and Zno/clay Ncmentioning
confidence: 93%
“…The empirical equation established by Freundlich is as follows (Eq. ( 9)): q e ¼ K F :C 1=n e (9) where K, F , and n are the Freundlich constants, related, respectively, to the adsorption capacity and its intensity. Applying this equation in its logarithmic form to the experimental data leads to the values of these constants from the y-intercept and the slope of the following line (Eq.…”
Section: Freundlich Modelmentioning
confidence: 99%
“…Among the few fields of application, bentonite can be used for the purification of gases [1], the elimination of radioactive elements [2,3], the elimination of pesticides [4], and the elimination of phenol. This pollutant was removed by variety of clays and modified clay as the bentonite [5], the clinoptilolite [6], the composite of silica [7], the silica/hydrotalcite [8], the natural clay [9], the Montmorillonite, Clinoptilolite and Hydrotalcite [10], the hectorite [11], the untreated coffee wastes [12], the lignite [13], the zeolite X/activated carbon [14], the shells of eggs [15,16] and the chitin/chitosan [16][17][18].…”
Section: Introductionmentioning
confidence: 99%